FOAM GLASS GRAVEL FROM RECYCLED GLASS WASTE PRODUCED WITH THE MICROWAVE ENERGY - Lucian Păunescu; Marius Florin Drăgoescu; Sorin Mircea Axinte (Nonconventional Technologies Review, 2020)
The results of the research in the field of microwave energy application in the process of manufacturing foam glass gravel from colored glass waste, calcium carbonate as a foaming agent, borax as a fluxing agent and sodium silicate solution as a binder are presented in the paper. The thermal process of sintering/ foaming the powder mixture was carried out in a 0.8 kW-domestic microwave oven adapted for high temperature operation. The foamed product at 845 ºC, with 1.5% calcium carbonate, 7% borax and 8% sodium silicate, reached the highest value of compressive strength (9.5 MPa), thermal conductivity 0.105 W/ m·k, apparent density 0.80 g/ cm3 and a homogeneous distribution of pores in the material  structure with dimensions below 1 mm.